1978-1979 ネン, ナンキョクカイ インドヨウ ク ニ オケル クロロフィルα ブンプ - 福地, 光男; フクチ, ミツオ; 田村, 清一; タムラ, セイイチ; Fukuchi, Mitsuo; Tamura, Seiichi (1982)
P(論文) 1978-1979年, 第20次日本南極地域観測隊にて, 南極海インド洋区におけるクロロフィルa量の水平・垂直分布を調査した。12月中旬に東経110度から90度へかけ南緯34度から60度への南下航路上, 12月下旬～1月上旬に南緯60度以南域を東経90度から39度へかけての西方航路上, および2月下旬～3月上旬に東経40度から51度へかけ南緯65度から34度への北上航路上において, 2時間間隔を含む表面観測を行った。北上航路上の南緯52度以南域では, 6観測点にて水深500mまでの垂直分布を調べた。南下航路上では南極収束線域に高クロロフィルa量(1.0mg/m^3以上)がみられたが, 北上航路上では亜熱帯収束線域に0.5mg/m^3以上の値がみられた。両航路上における表面クロロフィルa量の緯度変化の相異から, 植物プランクトンの季節変動が示唆された。西方航路上におけるクロロフィルa量の経度変化は, 湧昇現象に関連すると思われた。0-250m水柱内クロロフィルa現存量は, 16.8～39.4mg/m^2であり, 水深50～100m付近に弱い亜表層クロロフィル極大がみられた。 Horizontal and vertical distributions of chlorophyll a in the Indian sector of the Antarctic Ocean were investigated during the 20th Japanese Antarctic Research Expedition in 1978-1979. Surface observations including the two hours interval observation were carried out on the southward leg between 34°S, 110°E and 60°S, 90°E in middle December, on the westward leg between 90°and 39°E south of 60°S in late December to early January, and on the northward leg between 65°S, 40°E and 34°S, 51°E in late February to early March. Vertical observations down to a 500m depth were done at six stations on the northward leg south of 52°S latitude. While high surface chlorophyll a concentrations (more than 1.0mg/m^3) were seen around the Antarctic Convergence on the southward leg, high concentrations more than 0.5mg/m^3 were distributed around the Subtropical Convergence on the northward leg. Difference in the latitudinal variations of surface chlorophyll a between the two legs suggested the seasonal periodicity of phytoplankton. Longitudinal variation on the westward leg seemed to be related with the upwellings of water. Integrated chlorophyll a stocks for a 0-250m water column were in a range of 16.8-39.4mg/m^2 and a weak subsurface chlorophyll a maximum was seen around 50-100m depths. departmental bulletin paper